2017
DOI: 10.1177/1477153517725974
|View full text |Cite
|
Sign up to set email alerts
|

Human perceptions of colour rendition at different chromaticities

Abstract: An experiment was conducted to evaluate how perceptions of a light source’s colour quality depend upon colour rendition and chromaticity. Thirty-four participants each evaluated 50 lighting scenes in a 3.7 m by 5.5 m room filled with objects. The lighting scenes included five chromaticity groups, with 10 systematically-varied colour rendition conditions repeated in each group. Participants, who chromatically adapted to each chromaticity group, were asked to rate each scene on eight point scales for saturated-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 49 publications
5
56
0
Order By: Relevance
“…At 50, 100, 200, 480, 2000, and 5000 lx, all the stimuli that were selected by the observers to produce the most preferred color appearance of the artwork had different levels of chroma enhancement (i.e., Rg > 100). It corroborated the findings that sources with good color fidelity may not always be preferred and those with larger relative gamut areas within a certain range were preferred (Wei et al, 2014;Wei and Houser, 2017;Royer et al, 2017Royer et al, , 2018Jost-Boissard et al, 2014). Specifically, Rf, Rg, and Rcs,h16 of the most preferred stimulus that were selected under 50, 100,200,480,2000, and 5000 lx were within the range defined in the two recent studies (Royer et al, 2017(Royer et al, , 2018)-Rf ≥ 74, Rg ≥ 100, and 2% ≤ Rcs, h16 ≤ 16%, though they were carried out around 200 lx.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…At 50, 100, 200, 480, 2000, and 5000 lx, all the stimuli that were selected by the observers to produce the most preferred color appearance of the artwork had different levels of chroma enhancement (i.e., Rg > 100). It corroborated the findings that sources with good color fidelity may not always be preferred and those with larger relative gamut areas within a certain range were preferred (Wei et al, 2014;Wei and Houser, 2017;Royer et al, 2017Royer et al, , 2018Jost-Boissard et al, 2014). Specifically, Rf, Rg, and Rcs,h16 of the most preferred stimulus that were selected under 50, 100,200,480,2000, and 5000 lx were within the range defined in the two recent studies (Royer et al, 2017(Royer et al, , 2018)-Rf ≥ 74, Rg ≥ 100, and 2% ≤ Rcs, h16 ≤ 16%, though they were carried out around 200 lx.…”
Section: Discussionsupporting
confidence: 81%
“…Sources that have a larger gamut area have been found to produce preferred color appearance, especially if the chroma enhancement happens to red hues (Wei et al, 2014;Royer et al, 2017;Royer et al, 2016;Wei et al, 2017). Recently, three psychophysical studies (Royer et al, 2017(Royer et al, , 2018(Royer et al, , 2019 that systematically varied color fidelity, gamut area, and gamut shape within t he context of IES TM-30-15 Rf, Rg, and Color Vector Graphic were carried out. Royer et al proposed the criterion that Rf ≥ 74, Rg ≥ 100, and 2% ≤ Rcs,h16 ≤ 16% (Royer et al, 2017) and it was later relaxed to Rf ≥ 75, Rg ≥ 98, and -7% ≤ Rcs,h16 ≤ 15% (Royer et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the experiment presented in this paper, the effects of CCT cannot be isolated from Duv since they were not separately controlled in this study. Royer et al 21 found that the CCT by Duv interaction was significant for predicting colour preference. In their study, the effect of Duv on colour preference was negligible at 4300 K, but was important at 2700 K, where a source with negative Duv was less preferred than a source on the blackbody locus.…”
Section: Discussionmentioning
confidence: 99%
“…To fill this void, numerous research efforts have investigated the accuracy of the new measures and their relationships to subjective qualities of the lit environment. [4][5][6][7][8][9][10][11][12][13] While considerable effort has been made to understand correlations between color rendition measures and subjective evaluations of colour quality (i.e., colour preference, colour naturalness, colour vividness, colour acceptability), little attention has been given to establishing new colour rendition specification criteria, which are the primary mechanism by which colour quality is evaluated in practical applications by entities such as the IES, United States Environmental Protection Agency (EPA), the DesignLights Consortium (DLC), the state of California, International Organization for Standardization (ISO) or the Chartered Institution of Building Services Engineers (CIBSE). Establishing colour rendition specification criteria requires detailed consideration of their purpose and level of stringency, among many other factors that influence the type of measures included and their threshold values.…”
Section: Introductionmentioning
confidence: 99%